The politics of federal prosecution - Boyd, Christina L. (Oxford University Press, 2021)
Federal prosecution yesterday and today -- Confirming U.S. attorneys -- Departures & removals -- Theorizing political responsiveness in prosecutorial decision making -- To prosecute or not : prosecutors as agenda setters -- The charging & bargaining decisions -- Criminal asset forfeiture as a political tool.